2021
DOI: 10.3390/v13091864
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Coevolutionary Adaptations across Time and Space in Mouse Gammaretroviruses and Three Restrictive Host Factors

Abstract: The classical laboratory mouse strains are genetic mosaics of three Mus musculus subspecies that occupy distinct regions of Eurasia. These strains and subspecies carry infectious and endogenous mouse leukemia viruses (MLVs) that can be pathogenic and mutagenic. MLVs evolved in concert with restrictive host factors with some under positive selection, including the XPR1 receptor for xenotropic/polytropic MLVs (X/P-MLVs) and the post-entry restriction factor Fv1. Since positive selection marks host-pathogen genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 106 publications
(160 reference statements)
1
4
0
Order By: Relevance
“…Previous studies have demonstrated that the Fv1 b allele, which lacks the 1.3-kb deletion commonly found in the subspecies domesticus and musculus, is observed with high frequency in the subspecies castaneus and Japanese samples (Boso et al 2021). We confirmed that the deletion started from Chr4:147,870,288 (GRCm38) and was 1.2 kb in length, resulting in truncation of the C-terminal region of Fv1 (Supplemental Method 4).…”
Section: Selection During Admixture In the Japanese Populationsupporting
confidence: 81%
“…Previous studies have demonstrated that the Fv1 b allele, which lacks the 1.3-kb deletion commonly found in the subspecies domesticus and musculus, is observed with high frequency in the subspecies castaneus and Japanese samples (Boso et al 2021). We confirmed that the deletion started from Chr4:147,870,288 (GRCm38) and was 1.2 kb in length, resulting in truncation of the C-terminal region of Fv1 (Supplemental Method 4).…”
Section: Selection During Admixture In the Japanese Populationsupporting
confidence: 81%
“…Indeed, our screening accurately identified the retroelement-like Fv1 (Friend virus susceptibility protein 1) gene, an antiviral factor (Best et al 1996) as an castaneus -ancestry enriched gene in Japan. Previous studies have demonstrated that the Fv1 b allele, which lacks the 1.3-kb-length deletion commonly found in the subspecies domesticus and musculus , is observed with high frequency in the subspecies castaneus and the Japanese samples (Boso et al 2021). We confirmed that the deletion started from chr4:147,870,288 (GRCm38) and had 1.2 kb in length, resulting in the truncation of C-terminal region of Fv1 .…”
Section: Resultsmentioning
confidence: 99%
“…There are a few studies that have examined the potential impact of gammretroviruses on the evolution of the genes that encode their cognate receptors [ 249 , 250 , 251 ]. There are now several examples of SLC receptors that are used by multiple retroviruses ( Table 1 ), as well as cases where the receptors used in the deep past by ancient ERV Env have been identified [ 50 , 72 , 188 , 206 , 214 , 221 , 222 ].…”
Section: Discussionmentioning
confidence: 99%